Constraining the time of construction of the irrigation system of Tell Hujayrat al-Ghuzlan near Aqaba, Jordan, using high-resolution optically stimulated luminescence (HR-OSL) dating - Rhodius, Christiane; Kadereit, Annette (Archaeological and anthropological sciences, 2017)
Tell Hujayrat al-Ghuzlan, situated at the northern periphery of modern Aqaba in southern Jordan, is one of the most important sites in Levantine archeology spanning the transitional period from late Chalcolithic to Early Bronze Age times. Numerous stone structures spread out in the surrounding area of the prehistoric settlement were interpreted as the remains of a complex hydro-technical system constructed for water supply of the settlement, agriculture, and craft production. Although construction of the water management system in prehistoric times seems likely, this hypothesis could not be proofed, as archeological evidence is missing and direct dating of the structures is not possible with established dating techniques. But the chronological placement of the irrigation system is essential to evaluate the settlement site appropriately within a wider socioeconomic context. Therefore, here, a feasibility study was carried out to test whether it is possible to date the last exposure of the stone surfaces of the irrigation system to daylight, as expected to occur during construction or repair works. For age determination, the high-resolution optically stimulated luminescence (HR-OSL) dating technique was applied. Five samples were dated, three of them from different hydro-technical components. The HR-OSL ages represent likely man-made as well as non-intentional or natural events. In summary, the results indicate that the water management system was in use in Early Bronze Age times, thus providing a minimum age for the time of construction.
First Online: 07 September 2015
Gesehen am 29.05.2018